Well-differentiated epithelial thyroid cancer management in the Asia Pacific region: A report and clinical practice guideline - Felix Sundram (2018)
Context: Thyroid cancer is among the 10 most common malignancies in populations in the Asia Pacific region, where access to various relevant health care resources varies widely. Objective: An expert consensus conference was held to define regional patterns of practice and guidelines for optimal management of well-differentiated epithelial thyroid carcinomas. Results: Practice patterns vary from country to country, as would be anticipated form their variety of ethnic and racial populations, health care systems, economies, and cultures. Thyroid cancer care is provided by a number of medical and surgical specialists, usually including endocrinologists. The thyroid surgical skills, experience, and outcomes vary widely in the region. Radioiodine is available, to a greater or lesser extent, is almost all countries. Laboratory services for thyroid function monitoring are universally accessible; thyroglobulin assays are available in most countries. Recombinant thyrotropin is approved for use in only two countries, but can be accessed in some others on a "named patient" compassionate need basis. Access to advanced imaging, for example, positron emission tomography (PET) scanning, is limited to a few countries. Conclusions: In light of these realities, appropriate strategies for initial treatment and postoperative monitoring of patients with thyroid cancer have been defined, and these are presented and discussed. © Mary Ann Liebert, Inc.